The Enemy’s Brides: Dionysius of Halicarnassus on the Abduction of the Sabine Women - Poletti, Beatrice (Histos, 2021)
Unlike other ancient sources focusing on the origin of Roman marriage, Dionysius of Halicarnassus read the abduction of the Sabine Women as a story to extol Roman foreign policy, based as it was on the principle of φιλανθρωπία as well as the foresight and political wisdom of the Roman ruling class. Romulus as a king-legislator and the Roman Senate are the real protagonists of the episode; the abducted women are bereft of, or given, agency according to their social and civic status: at first passive foreigners, they become fully sentient political beings after gaining Roman citizenship through marriage.